Russian Orthodox Church and science. Debates on the theory of evolution in 19th and 20th Centuries - Obolevitch, Teresa (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2007)
In this article the author considers an attitude of the Russian Orthodox Church towards the theory of evolution beginning with the year of publication of Darwin ’The Evolution of Species’ until contemporary times. The orthodox theology relies upon the thought of Greek Fathers of the Church who emphasized a difference between the incomprehensible essence of God and His actions (energies), by which He reveals Himself in the created world. In the light of the above conception the Orthodox Church acknowledges every scientific theory as an reflexion of this revelation, if only it doesn’t trespass its relevant boundaries. Thus, the Russian Orthodox Church has never condemned the evolution theory itself, although some of her theologians have been criticizing some of its aspects. In the last part the author presents contemporary polemics between orthodox evolutionists and creationists. He also suggests some insight into their arguments exposing their limitations.In this article the author considers an attitude of the Russian Orthodox Church towards the theory of evolution beginning with the year of publication of Darwin ’The Evolution of Species’ until contemporary times. The orthodox theology relies upon the thought of Greek Fathers of the Church who emphasized a difference between the incomprehensible essence of God and His actions (energies), by which He reveals Himself in the created world. In the light of the above conception the Orthodox Church acknowledges every scientific theory as an reflexion of this revelation, if only it doesn’t trespass its relevant boundaries. Thus, the Russian Orthodox Church has never condemned the evolution theory itself, although some of her theologians have been criticizing some of its aspects. In the last part the author presents contemporary polemics between orthodox evolutionists and creationists. He also suggests some insight into their arguments exposing their limitations.